2013
DOI: 10.1016/j.jbiomech.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different inter-pad distances on the determination of active drag using the Measuring Active Drag system

Abstract: The Measuring Active Drag (MAD) system was developed to determine active drag in swimming by measuring the push-off force exerted at fixed pads placed below the waterline. The imposed inter-pad distance, which to date has been kept constant while using the MAD system, could affect the active drag because it requires the use of different stroke frequencies. The aim of the present study was therefore to determine the effect of inter-pad distance on active drag at a given speed. In particular, drag-velocity curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Using this approach, the swimmer's technique might present some alterations since the push-off is made from fixed pads rather than from moving water. However, considering that this circumstance seems to not influence the determination of drag [25], and since other methodologies have important limitations on its assessment -they are indirect evaluations [8], restricted to maximal velocities [16] and limited to a stable position during gliding from the wall [19] -we have favoured the MAD-system procedure. As expected, results were in line with the literature [6,30,31], showing an approximately quadratic increase in active drag with swimming velocity for both unimpeded and with snorkel conditions.…”
Section: Discussion ▼mentioning
confidence: 99%
“…Using this approach, the swimmer's technique might present some alterations since the push-off is made from fixed pads rather than from moving water. However, considering that this circumstance seems to not influence the determination of drag [25], and since other methodologies have important limitations on its assessment -they are indirect evaluations [8], restricted to maximal velocities [16] and limited to a stable position during gliding from the wall [19] -we have favoured the MAD-system procedure. As expected, results were in line with the literature [6,30,31], showing an approximately quadratic increase in active drag with swimming velocity for both unimpeded and with snorkel conditions.…”
Section: Discussion ▼mentioning
confidence: 99%
“…In the present study, the MAD system was used to determine power output and drag. One of the limitations of the MAD system is that the push-off pads on the MAD system were placed at a fixed inter-pad distance of 1.35 m. Although it was found that different inter-pad distances did not affect the measured drag (Schreven et al, 2013 ), it has not been studied to date whether the maximal speed achieved on the MAD system varies with inter-pad distance. Therefore, it cannot be excluded that by using a different inter-pad distance, the correlation with swimming speed would have been different.…”
Section: Discussionmentioning
confidence: 99%
“…Also, despite the similarity of electromyography patterns obtained during MAD-System and normal front crawl swimming (Clarys et al, 1988), it is questionable whether the pulling on the paddles replicates the normal swimming action or restricts normal stroke mechanics . Schreven et al (2013) further assessed the reliability of the set inter-pad distances of the MAD-System based on anthropometric characteristics of a small sample of participants (n=11) swimming at sub-maximal speed and concluded that a fixed distance could be used. Whilst adding to the scope of studies utilising the MAD-System, it should be noted that the translatability of this finding to swimming in a competition setting requires further investigation.…”
Section: Overview Of Active Drag Methodsmentioning
confidence: 99%